Tc 99m labelled leucocyte scintigraphy in ulcerative colitis - Enver DOLAR; Sıddık GÜLSÜN; Macit GÜLTEN; Giray NAK; Mahmut ÖZTÜRK; Tayyar AKBUDAR; Faruk MEMİK (Turkish Journal of Gastroenterology, 2020)
-